PENGARUH KUALITAS ASET, LIKUIDITAS DAN RENTABILITAS TERHADAP KECUKUPAN MODAL PADA PERUSAHAAN PERBANKAN YANG LISTING DI BEI PERIODE 2015-2017 - Fina Hikmatul Insaniyah; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to determine how the influence of asset quality, liquidity and rentability on capital adequacy in banking companies listed on the Stock Exchange for the period 2015-2017. The variables used in this study are capital adequacy variables (dependent variables), while the independent variables namely asset quality are measured using the NPL ratio (Net Performing Loan), Liquidity is measured using the LDR (Loan to Deposit Ratio) ratio and Rent ability is measured using the ROA (Return On Asset). The data analysis technique used is multiple linear, complete with normality tests and classic assumptions (multicollinearity, heteroscedasticity, autocorrelation). The hypothesis is tested using the t-test and F test with a significance level of 5%. Based on the results of the partial test using the t-test, it is known that the Asset Quality (NPL) variable has a negative effect on capital adequacy in banking companies listing on the Indonesia Stock Exchange for the periode 2015-2017, Liquidity (LDR) ) variable has a negative effect on capital adequacy in banking companies listing on the Indonesia Stock Exchange for the periode 2015-2017 and Rent ability (ROA) ) variable has a negative effect on capital adequacy in banking companies listing on the Indonesia Stock Exchange for the periode 2015-2017. Keywords: Asset Quality, Liquidity, Rent ability, Capital Adequacy